Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Let's solve the expression step by step to find the value of [tex]\(\frac{4}{3} \tan^2 30^{\circ} + \sin^2 60^{\circ} + \frac{3}{4} \tan^2 60^{\circ} - 2 \tan^2 45^{\circ}\)[/tex].
1. Calculate [tex]\(\tan^2 30^{\circ}\)[/tex]:
First, remember that [tex]\(\tan 30^{\circ} = \frac{1}{\sqrt{3}}\)[/tex].
[tex]\[ \tan^2 30^{\circ} = \left( \frac{1}{\sqrt{3}} \right)^2 = \frac{1}{3} \][/tex]
Now calculate [tex]\(\frac{4}{3} \tan^2 30^{\circ}\)[/tex]:
[tex]\[ \frac{4}{3} \tan^2 30^{\circ} = \frac{4}{3} \cdot \frac{1}{3} = \frac{4}{9} \approx 0.444444 \][/tex]
2. Calculate [tex]\(\sin^2 60^{\circ}\)[/tex]:
Recall that [tex]\(\sin 60^{\circ} = \frac{\sqrt{3}}{2}\)[/tex].
[tex]\[ \sin^2 60^{\circ} = \left( \frac{\sqrt{3}}{2} \right)^2 = \frac{3}{4} = 0.75 \][/tex]
3. Calculate [tex]\(\tan^2 60^{\circ}\)[/tex]:
We know [tex]\(\tan 60^{\circ} = \sqrt{3}\)[/tex].
[tex]\[ \tan^2 60^{\circ} = (\sqrt{3})^2 = 3 \][/tex]
Now calculate [tex]\(\frac{3}{4} \tan^2 60^{\circ}\)[/tex]:
[tex]\[ \frac{3}{4} \tan^2 60^{\circ} = \frac{3}{4} \cdot 3 = \frac{9}{4} = 2.25 \][/tex]
4. Calculate [tex]\(\tan^2 45^{\circ}\)[/tex]:
Remember that [tex]\(\tan 45^{\circ} = 1\)[/tex].
[tex]\[ \tan^2 45^{\circ} = 1^2 = 1 \][/tex]
Now calculate [tex]\(2 \tan^2 45^{\circ}\)[/tex]:
[tex]\[ 2 \tan^2 45^{\circ} = 2 \cdot 1 = 2 \][/tex]
5. Combine all terms:
Now, add the terms together and subtract the last term:
[tex]\[ \frac{4}{3} \tan^2 30^{\circ} + \sin^2 60^{\circ} + \frac{3}{4} \tan^2 60^{\circ} - 2 \tan^2 45^{\circ} \][/tex]
Substituting the calculated values:
[tex]\[ 0.444444 + 0.75 + 2.25 - 2 \][/tex]
Simplify this expression:
[tex]\[ 0.444444 + 0.75 + 2.25 - 2 = 1.444444 \][/tex]
So, the value of the given expression is [tex]\(1.444444\)[/tex].
1. Calculate [tex]\(\tan^2 30^{\circ}\)[/tex]:
First, remember that [tex]\(\tan 30^{\circ} = \frac{1}{\sqrt{3}}\)[/tex].
[tex]\[ \tan^2 30^{\circ} = \left( \frac{1}{\sqrt{3}} \right)^2 = \frac{1}{3} \][/tex]
Now calculate [tex]\(\frac{4}{3} \tan^2 30^{\circ}\)[/tex]:
[tex]\[ \frac{4}{3} \tan^2 30^{\circ} = \frac{4}{3} \cdot \frac{1}{3} = \frac{4}{9} \approx 0.444444 \][/tex]
2. Calculate [tex]\(\sin^2 60^{\circ}\)[/tex]:
Recall that [tex]\(\sin 60^{\circ} = \frac{\sqrt{3}}{2}\)[/tex].
[tex]\[ \sin^2 60^{\circ} = \left( \frac{\sqrt{3}}{2} \right)^2 = \frac{3}{4} = 0.75 \][/tex]
3. Calculate [tex]\(\tan^2 60^{\circ}\)[/tex]:
We know [tex]\(\tan 60^{\circ} = \sqrt{3}\)[/tex].
[tex]\[ \tan^2 60^{\circ} = (\sqrt{3})^2 = 3 \][/tex]
Now calculate [tex]\(\frac{3}{4} \tan^2 60^{\circ}\)[/tex]:
[tex]\[ \frac{3}{4} \tan^2 60^{\circ} = \frac{3}{4} \cdot 3 = \frac{9}{4} = 2.25 \][/tex]
4. Calculate [tex]\(\tan^2 45^{\circ}\)[/tex]:
Remember that [tex]\(\tan 45^{\circ} = 1\)[/tex].
[tex]\[ \tan^2 45^{\circ} = 1^2 = 1 \][/tex]
Now calculate [tex]\(2 \tan^2 45^{\circ}\)[/tex]:
[tex]\[ 2 \tan^2 45^{\circ} = 2 \cdot 1 = 2 \][/tex]
5. Combine all terms:
Now, add the terms together and subtract the last term:
[tex]\[ \frac{4}{3} \tan^2 30^{\circ} + \sin^2 60^{\circ} + \frac{3}{4} \tan^2 60^{\circ} - 2 \tan^2 45^{\circ} \][/tex]
Substituting the calculated values:
[tex]\[ 0.444444 + 0.75 + 2.25 - 2 \][/tex]
Simplify this expression:
[tex]\[ 0.444444 + 0.75 + 2.25 - 2 = 1.444444 \][/tex]
So, the value of the given expression is [tex]\(1.444444\)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.